Guía para el diseño integral de estaciones intermodales en Bogotá: caso de estudio: primera línea del metro de Bogotá - Bastilla Rojas, Silvia Marcela (Universidad Antonio Nariño, 2024)
In the context of increasing urbanization and the need for efficient and sustainable transportation systems, Bogotá faces the challenge of redesigning its urban mobility to improve the quality of life of its inhabitants. The First Line of the Bogotá Metro (PLMB) emerges as a response to these challenges, promising to transform the city's transportation landscape through the integration of various mobility systems. However, the implementation of mass transport infrastructure like the PLMB requires not only technical and financial innovation but also an integral approach that considers intermodality as a fundamental pillar for effective and equitable urban mobility